Hanging-associated out-of-hospital cardiac arrests in Melbourne, Australia - Deasy, C.; Bray, Janet; Smith, K.; Bernard, S.; Cameron, P. (2013)
Introduction: Hanging is an infrequent but devastating cause of out-of-hospital cardiac arrest (OHCA). We determine the characteristics and outcomes of hanging-associated OHCA in Melbourne Australia. Methods: A 10-year retrospective case review of all adult hangings (aged =16 years) associated with OHCA, was conducted using data from the Victorian Ambulance Cardiac Arrest Registry. Results: Between 2000 and 2009, the emergency medical service (EMS) attended 33 178 adult OHCAs of which 1321 (4%) had hanging as the aetiology. The median age (IQR) of hanging-associated OHCA cases was 39 (29-51) years and 1162 were men (88%). The first recorded rhythm by EMS was asystole seen in 1276 (75.5%) patients, pulseless electrical activity (PEA) in 38 (13.4%) cases and ventricular fibrillation in 7 cases (0.5%). EMS attempted resuscitation in 208 (15.7%) patients of whom 61 (29.3%) achieved return of spontaneous circulation (ROSC) and were transported, and 7 (3.3%) survived to hospital discharge. Hanging-associated OHCAs were younger (median (IQR) 38 (29-51) years versus 74 (61-82) years, p<0.001), less likely to have a shockable rhythm (0.5% vs 17.2%, p<0.001), receive bystander cardiopulmonary resuscitation (14.1% vs 25.5%, p<0.001) or an attempted resuscitation by EMS (15.7% vs 36.1%, p<0.001) compared with OHCA cases with an aetiology of 'presumed cardiac' arrest. Multivariable logistic regression identified factors associated with EMS decision to attempt resuscitation; the adjusted OR (95% CI) for 'presence of bystander cardiopulmonary resuscitation' was 15.8 (10.70-23.30) and for 'witnessed arrest' was 5.26 (1.17-23.30). Conclusion: Attempted resuscitation was not always futile with a survival of 3.3%. A preventive focus is needed.